Self Control Santriwati Pondok Pesantren Tahfidhul Qur’an Roudhotul Qur’an Panekan Magetan - Lia Amalia Syihab; Nihayatul Afifah (At-Tafasir: Journal of Al-Qur'an Studies and Contextual Tafsir, 2025)
This qualitative study investigates the self-control of female Qur'an memorization students at PTQ Roudhotul Qur'an, crucial for their success given the demands of memorization and the need for consistent practice. Despite individual differences in memory, effective self-control is key. The research focused on three core aspects of self-control: behavioral, cognitive, and decisional control. This study was designed using a descriptive qualitative method. Data collection was carried out by observation and interviews. The participants in this study were three female students who were teenagers who were selected through the purposive sampling technique. The data from the results of this study were then analyzed using the Miles and Huberman analysis model which includes data reduction, data display and conclusions or data verification. Findings indicate that the students exhibited good self-control across all aspects. In behavioral control, they demonstrated situational appropriateness, responsibility, and adherence to boarding school rules. For cognitive control, they showed strong abilities in thinking, understanding, and processing their surroundings. Lastly, their decision control was robust, reflecting their capacity to make agreed-upon choices and select opportunities for action. These findings highlight the significant role of self-control in supporting the memorization journey of these students.